Relativistic Time Transfer for Inter-satellite Links - Xie, Yi (Frontiers in Astronomy and Space Sciences, 2016)
Inter-Satellite links (ISLs) will be an important technique for a global navigation satellite system (GNSS) in the future. Based on the principles of general relativity, the time transfer in an ISL is modeled and the algorithm for onboard computation is described. It is found, in general, satellites with circular orbits and identical semi-major axes can benefit inter-satellite time transfer by canceling out terms associated with the transformations between the proper times and the Geocentric Coordinate Time. For a GPS-like GNSS, the Shapiro delay is as large as 0.1 ns when the ISL passes at the limb of the Earth. However, in more realistic cases, this value will decrease to about 50 ps.